PENGARUH GLOBALISASI TERHADAP ”FORUK” DI TANIMBAR - Batlayeri, Hilarius (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2014)
Globalisation is a phenomenon which nowadays occurs in people‘s everyday life. This globalisation is developping at a high speed, since it is supported by the ever advancing technologies of information and communication. Globalisation has both positive and negative impact on culture, especially on Foruk. Foruk is a type of culture which is of great value; however, it is more and more vanishing from people‘s memory. By making use of advanced technologies in the field of information and communication Foruk can be restored in Tanimbar.